2018
DOI: 10.1177/1756286418804785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of motor imagery and electrical stimulation on upper extremity motor function in patients with chronic stroke: preliminary results

Abstract: Background:The combination of motor imagery (MI) and afferent input with electrical stimulation (ES) enhances the excitability of the corticospinal tract compared with motor imagery alone or electrical stimulation alone. However, its therapeutic effect is unknown in patients with hemiparetic stroke. We performed a preliminary examination of the therapeutic effects of MI + ES on upper extremity (UE) motor function in patients with chronic stroke.Methods:A total of 10 patients with chronic stroke demonstrating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Similar acute effects were shown using combined motor imagery and electrical stimulation of the lower-limbs [ 137 ]. Preliminary results with chronic stroke patients also suggest that applying electrical stimulation in combination with motor imagery over the course of 10 days may possibly improve upper-limb function after the intervention cessation [ 106 ]. Tasks involving motor imagery and/or action observation can produce reliable and muscle-specific excitability of corticospinal responses in the upper-limbs (e.g., [ 39 , 138 ]).…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%
“…Similar acute effects were shown using combined motor imagery and electrical stimulation of the lower-limbs [ 137 ]. Preliminary results with chronic stroke patients also suggest that applying electrical stimulation in combination with motor imagery over the course of 10 days may possibly improve upper-limb function after the intervention cessation [ 106 ]. Tasks involving motor imagery and/or action observation can produce reliable and muscle-specific excitability of corticospinal responses in the upper-limbs (e.g., [ 39 , 138 ]).…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervementioning
confidence: 99%
“…This review was conducted to determine the effects of motor imagery on the recovery of upper limb function in persons affected by stroke. Several studies have reported that the effectiveness of motor imagery training as well as motor imagery with brain-computer interface and motor imagery triggered electrical stimulation on upper extremity function in activities of daily living and functional activities for stroke survivors [14,22,[27][28][29]. They provided several therapeutic types to be conducted with motor imagery to improve upper limb function.…”
Section: Discussionmentioning
confidence: 99%
“…Motor imagery of movement is an active, cognitive process used to investigate the content and structure of covert processes that precede the execution of action, and so the training protocol will provide a relatively lower level of mo-tor function or acute stage of the disease following stroke [33][34][35]. When paired with conventional therapeutic interventions, motor imagery training can be as effective as pure conventional therapeutic interventions for recovery following stroke [8,14,27,35]. The results of this review also showed that motor imagery training with other therapeutic interventions based on motor function could exhibit positive effects on upper limb function following stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a secondary analysis of data from previous randomized, controlled trials or clinical trials (23)(24)(25)(26). Outlines of each study, including ethical approval and clinical trial registration numbers, are provided as Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%